AB0013 HLA ASSOCIATION WITH SYSTEMIC SCLEROSIS (SSc) IN NORTH INDIAN POPULATION AND FAMILIAL INHERITANCE PATTERNS - Machhua, S.; Minz, R.; Sharma, S. K.; Singh, H.; Kumar, Y.; Anand, S.; Handa, S.; Singh, S. (Annals of the rheumatic diseases, 2020)
Background:It is widely believed that SSc develops in an individual with a permissive genetic makeup.Genetic influences have long been suspected to impact SSc. In families with a history of SSc, the incidence of disease can range from 1.5 to 1.7% (1). There are several reports of familial occurrence and certain alleles of the HLA system have been associated with the disease (2).No Indian data pertaining to genetic basis of systemic sclerosis is present. Understanding the genetic basis of the disease will help us in defining the biomarkers of the disease in the population that can help in early diagnosis and prognosis.Objectives:To study HLA association with Systemic sclerosis (SSc) in North Indian Population and its genetic susceptibility to familial systemic sclerosis.Methods:A total of 150 SSc patients diagnosed by following ACR and EULAR criteria and 150 control subjects, were genotyped for HLA-A, B, DRB1, DQB1 loci by Luminex® 200 Instrument (USA). The association of alleles with disease susceptibility was tested by Chi-square test and Fisher’s exact test.HLA Typing for HLA class I (A, B, C) and II(DR,DQ,DP) for familial study of systemic sclerosis in 2 families was performed by Next Generation Sequencing(NGS) with illumina MiniSeq using MIA FORA NGS Kits from IMMUCOR. Antinuclear patterns (ANA) and specific antibodies were detected by indirect Immunofluorescence and Immunoblot (Euroline, Germany).Results:Strong disease associations were observed for haplotypes A*24(OR=1.7;< 0.02), A*32(OR=2.8;< 0.02), B*35(OR=1.7;< 0.03), DRB1*11(OR=2.1;< 0.007). The reduced frequencies of haplotypes A*68(P< 0.05), DRB1*10(P< 0.05), DRB1*12 (P<0.00) among patients suggested a protective association. There was no statistical association found with HLA DQB*1.Through NGS we observed that in the 1st family haplotypes HLA –A*11, 32, 24; B* 51, 55, 35; C*-14, 04; DRB1*15, 04; DQB1*05, 03; DPB1*04, 26 appears in affected family members with serological abnormalities.In the 2nd family both mother and daughter had same set of haplotypes except DQB1 with serological abnormalities. The haplotypes DPB1*04 was present in all the diseased individuals of both the families (Fig. 1 and table 1).Table 1.NGS HLA typing reportABCDRB1DQB1DPB1F111 2435 1504 0415 1505 0502 26F211 3251 5514 0415 0405 0304 04F311 2435 5504 0415 1505 0526 04F432 1151 1514 0415 0405 0302 04F524 3335 4404 0715 0705 0226 14F611 2435 5504 0415 1505 0504 26F711 2435 5504 0415 1505 0504 26F824 3251 3514 0404 1503 0526 04F911 3251 5514 0415 0405 0304 04F1011 3344 5207 1211 0702 0304 13F1111 3344 5207 1211 0703 0304 13Fig. 1Conclusion:The risk alleles A*24, 32; B*35; DRB1*11 were found to be associated with North Indian cohort of SSc, while the protecting alleles were A*68; DRB1*10, 12.These risk alleles were present in the SSc affected family members and the protective alleles were absent in the same. Surprisingly, even healthy members carried the same risk alleles but did not manifest the disease or have serological evidence of the same. We have not excluded occurrence of disease at a later age, as presently the healthy siblings are young. Thus our study indicates that though HLA association are found with SSc but many other factors like HLA (HLA *C, DPB1*) or non HLA genes as wells as epigenetic factors might also play a role in disease manifestation and severity.References:[1]Luo Y, Wang Y, Wang Q, et al. Systemic sclerosis: genetics and epigenetics. J Autoimmun.2013; 41:161–67.[2]de Juan MD1, Belzunegui J, Belmonte I, Barado J, Figueroa M, Cancio J, Vidal S, Cuadrado E. An immunogenetic study of familial scleroderma. Ann Rheum Dis. 1994 Sep; 53(9):614-7.Acknowledgments:The technical help of Mr.Manoj Kumar and Mr.Vinkesh are hereby gratefully acknowledged Indian Council of Medical Research(Funding of Fellowship)Disclosure of Interests:None declared